Numerical simulation of single phase flow in a flotation machine - Szczygieł, Ireneusz; Fic, Adam; Sachajdak, Andrzej; Rojczyk, Marek; Buliński, Zbigniew; Mańka, Adam (Computer Assisted Methods in Engineering and Science, 2017)
In the paper, the numerical model of the flow phenomena in the flotation machine is presented. The process of flotation consists of a number of phenomena which provide serious numerical difficulties. One can enumerate rotation, two phase flow, foam formation etc. To the knowledge of authors there is no complete numerical model available for the flotation machine. The long-term task of the project is to create a complete model of the machine. Such a model would be very helpful in the process of construction and modernization of the flotation machine. As it was mentioned, due to difficulties connected with modelling the flotation phenomena, only a few aspects of the process were taken under consideration. In the paper, a single phase flow of water is considered. The efficiency of the flotation process strongly depends on the fluid flow field in the machine. The level of mixing the fractions and air bubbles strongly depends on the velocity field of the water, so the proper model of fluid flow is of great practical importance. This paper presents preliminary results of mathematical modelling. The commercial package ANSYS Fluent was utilized for the analysis. The results were compared with the measurements performed on the small scale model of the machine. Obtained results are satisfying and encouraging for further development.